Analisis Pengaruh Gaya Kepemimpinan dan Stres Kerja Terhadap Work-Life Balance Karyawan Swasta di Cirebon - Bilal Dewansyah; Ni Wayan Fitriana A.L; Taufan Huneman (Komunitas Dosen Indonesia, 2024)
Work-life balance is one of the important things for employees' lives, Work-life balance can affect various things and can be influenced by various things, such as leadership style and work stress. This research aims to analyze the influence of leadership style and work stress on the Work-life balance of private employees in Cirebon. This type of research is quantitative research with a sample size of 100 respondents. The research method was carried out by survey using Google Form with a five-point Likert scale. This research uses SmartPLS 4 as an analysis tool. The results of this research conclude that (1) leadership style has a positive and significant effect on Work-life balance. (2) work stress has a negative and significant effect on Work-life balance. (3) leadership style and work stress simultaneously influence Work-life balance. The influence of leadership style and work stress on Work-life balance is 27%, and the other 73% is influenced by other variables.